Persepsi Pemerintah Daerah terhadap Partisipasi Masyarakat dan Transparansi Akuntabilitas Anggaran - Pudjiastuti, Irjani; ., Nurdhiana (Jurnal Ilmu Ekonomi ASET, 2010)
The purpose of this research was to know the response of local government ofCentral Java Province to society participation and the transparency and accountability incompilation of APBD. Population in this research was all committee of Budget compiler whichwas consisted of 32 people, and sample taken by census, and also the data analysis method inthis research by using scale of interval class. The result of this research indicated that perceptionof local government of Central Java Province to society participation in budget compilationin very good criterion with average of weight 29,50. and the perception of local government ofCentral Java Province to transparency and accountability related to compilation of APBD incriterion very good with average of weight 21,25. So that there by perception of LocalGovernment of Central Java Province to society participation in compilation of budget andpublic policy transparency in budget compilation was very good, so that it can be conductedthat people are active in participation of compilation of budget and activity of transparencyand accountability has been very transparent and accountable.Keywords : transparency, accountability, society participation.